Citra Perempuan dalam Antologi Puisi Rahi(i)m Karya Kedung Darma Romansha serta Implikasinya terhadap Pembelajaran Bahasa Indonesia di Sekolah - Feby Sonya; Slamet Triyadi; Imam Muhtarom (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to describe the image of women in the poems of the writer Kedung Darma Romansha and describe the results of the description of the meaning of the image of women by learning the Indonesian language, namely the subject of poetry appreciation in high school class X. The research method used is a descriptive qualitative method in the form of paradigms in word descriptions. -words to describe and analyze facts naturally and then interpret them appropriately. The results showed that: (1) the image of women, consisting of self-image and social image; 2) the image of women in the anthology of poetry entitled Rahi(i)m by Kedung Rama Romansha can be used as implications for learning Indonesian at school. Conclusions, (1) there is an image of women in the poem in the anthology entitled Rahi(i)m by Kedung Darma Romansha; 2) the implications of Rahi(i)m's poetry anthology with learning Indonesian at school is as a reference in the subject of poetry appreciation in high school class X. Keywords: Image of Women, Rahi(i)m, Indonesian Language Learning